1993
DOI: 10.1111/j.1432-1033.1993.tb17871.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin binding to its platelet receptor inhibits platelet aggregation

Abstract: A fluorescent lactotransferrin probe was prepared by coupling 5-( { [2-(carbhydrazino)methyl]-thio) acety1)amino fluorescein to aldehyde groups that were produced by a mild periodic-acid oxidation of the glycan moieties of lactotransferrin. In this manner, the receptor-binding site of the lactotransferrin remains active in contrast to the binding site of the lactotransferrin derivatized with fluorescein isothiocyanate. The fluorescent probe allowed us to characterize, by flow cytometry, the binding of lactotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…In contrast to our peptide, binding to these receptors was therefore saturable. Quite remarkably, regarding binding to the lymphocyte lactoferrin receptor and the platelet lactoferrin receptor, evidence has been obtained for the involvement of the loop domain corresponding to the lactoferrin-derived CPP (49,50). Competition experiments with our peptide for the binding of lactoferrin may thus help to better define ligand binding domains for other types of lactoferrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our peptide, binding to these receptors was therefore saturable. Quite remarkably, regarding binding to the lymphocyte lactoferrin receptor and the platelet lactoferrin receptor, evidence has been obtained for the involvement of the loop domain corresponding to the lactoferrin-derived CPP (49,50). Competition experiments with our peptide for the binding of lactoferrin may thus help to better define ligand binding domains for other types of lactoferrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which hLF peptides exert their bactericidal activity is not known. A number of antimicrobial peptides have been shown to bind cell wall components of gram-positive and gram-negative bacteria (19) and C. albicans (15), and lactoferrin receptors on a variety of cells have been described (17,30,36,37). Previous studies have shown that the cytotoxic activity of human neutrophil defensins l to 3 against C. albicans (29), bacteria (41), and tumor cells (31) is energy dependent.…”
mentioning
confidence: 99%
“…hLF (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in killing C. albicans, since it was necessary to use 10 times more hLF(21-31) than hLF(1-11) for a similar level of candidacidal activity. Next, to find out which N-terminal amino acids of hLF are essential in the candidacidal activity of the peptide comprising the first cationic domain, we compared the candidacidal activities of hLF(1-11) and fragments thereof.…”
mentioning
confidence: 99%
“…It has been reported that LF receptors are expressed on intestine, 1) monocytes, 2) osteoblasts, 3) PHAactivated lymphocytes, 4) PLTs, 5) and megakaryocytic cells. 6) LF levels in the serum of healthy donors are in the range of 2 to 7 mg/ml.…”
mentioning
confidence: 99%
“…9,10) To date, it has been reported that LF is involved in a variety of biological functions, such as cell growth and differentiation, [11][12][13] modulation of the inflammatory response, 14) anti-viral effects, 15) and regulation of myelopoiesis. 16,17) LF showed inhibitory effects on PLT aggregation by binding to the LF receptor which exists on the surface of PLTs, 5) but it is unclear whether LF can act on MKs though the LF receptor on the MKs. 6) Therefore, we assume that LF may contribute to differentiation of MKs as well as being involved in cell proliferation and differentiation.…”
mentioning
confidence: 99%